Effect of HLA-G5 Immune Checkpoint Molecule on the Expression of ILT-2, CD27, and CD38 in Splenic B cells. (12th May 2022) - Rohn, Hana; Lang, Cordula; Schramm, Sabine; Heinemann, Falko M.; Trilling, Mirko; Gäckler, Anja; Witzke, Oliver; Horn, Peter A.; Rebmann, Vera
Abstract : The human leukocyte antigen G (HLA-G) is an immune checkpoint molecule with a complex network of interactions with several inhibitory receptors. Although the effect of HLA-G on T cells and NK cells is well studied, the effect of HLA-G on B cells is still largely elusive. B cells are of particular interest in the context of the HLA-G-ILT-2 interaction because the ILT-2 receptor is constitutively expressed on most B cells, whereas it is only present on some subsets of T and NK cells. To characterize the effect of HLA-G5 molecules on B cells, we studied splenic B cells derived from cytomegalovirus (CMV) sero-positive donors after CMV stimulation with antigens in the presence and absence of soluble HLA-G5. In the presence of HLA-G5, increased expression of the ITIM-bearing Ig-like transcript (ILT-2) was observed on B cells, but its expression was not affected by stimulation with CMV antigens. Moreover, it became evident that HLA-G5 exposure resulted in a decreased expression of CD27 and CD38 and, accordingly, in lower proportions of CD19 + CD27 + CD38 + and higher proportions of CD19 + CD27 - CD38 - B cells. Taken together, our in vitro findings demonstrate that soluble HLA-G5 suppresses markers of B cell activation, suggesting that HLA-G5 has an impact on splenic B cell differentiation and activation. Based on these results, further investigation regarding the role of HLA-G as a prognostic factor and a potential therapeutic agent with respect to B cell function appears reasonable.